“GERAKAN ADVOKASI FORBALI DALAM UPAYA PENCABUTAN SK NOMOR 2138/02-CL/HK/2012 Tentang Izin Rencana Pemanfaatan dan Pengembangan Kawasan Perairan Teluk Benoa”. - Rambu Anarki, Fransiska Xaveriana Tamu; Erawan, I Ketut Putra; Jayanthi Mertha, A.A Sagung Mirah Mahaswari (Jurnal Nawala Politika, 2019)
ABSTRACT This research using qualitative descriptive method and purposive sampling technic approach. The successful of ForBALI social movement within revocation of S K number 2138/02-CL/HK/2012 about UtilizationwPlanning and Development of Benoa Bay Aquatic Area are using one theory: Charles Tilly Social Movement Theory. The theory of Charles Tilly’s Social Movement had been facilitating the ForBALI’s advocation about Benoa Bay reclamation policy. Discovering ForBALI advocation movement within Charles Tilly social movement namely campaign e and WUNC Display was the purpose of this research and furthermore been succeeded to urge the Governor of Bali for immediately to revoke SK of reclamation permit. The finding of this research was first, T imeline of SK number 2138/02-CL/HK/2012 had proven to violate the procedure. Second, the inconsistency act carried out by the Governor of Bali towards the SK about reclamation permission. Third, the accomplishment ForBALI’s advocation movement had been done through  social process involving campaign and WUNC Display.   Keywords : Benoa Bay, Reclamation, ForBALI, Social Movement, Advocation